Variety of therapeutic approaches to primary hyperhidrosis (HH) and botulinum toxin priority over other treatment options in this condition - a review - Pawlak, Igor; Perkowska, Klaudia; Kaźmierczak, Anna; Izdebska, Wiktoria; Sornek, Patrycja; Borkowska, Agata; Kiełb, Anna; Mich, Anna; Ciesielski, Radosław; Stanek, Jakub (Quality in Sport, 2024)
Introduction and purpose Hyperhidrosis (HH) is a medical conditions that affects more and more people every year. It is characterized by undue sweating without any temperature changes and significantly above the body’s thermoregulation needs. Primary hyperhidrosis is associated with genetic and psychological factors, as the etiology is not yet found. Treatment is aimed at the symptoms. Secondary hyperhidrosis happens as an adverse event of drugs taken by patient or is a part of neurological, endocrine or oncological diseases. Teratment should be focused on the main underlying disease. The quality of life of these patients is reduced and it affects their psychological health. This study inevstigates currently available methods of treatment. State of knowledge Various treatment options for hyperhidrosis range from topical aluminum salts for mild cases to oral anti-cholinergic agents for more severe conditions. Additional methods include iontophoresis, lasers like Nd:Yag, and botulinum toxin injections, known for their effectiveness. Surgical procedures such as Endoscopic Thoracic Sympathectomy, local skin excision, liposuction-curettage are also available for severe cases. Consultation with a healthcare provider is crucial to determine the most suitable treatment based on individual needs and preferences. Conclusions Literature provides valuable insights into hyperhidrosis and its treatments, emphasizing the importance of patient expectations and safety. Starting with topical aluminum salts for mild cases, treatments need to be reapplied regularly. Surgical options are considered if conservative treatments fail, but they come with potential risks. Botulinum toxin injections stand out for their efficacy, quick procedure, and the convenience of one or two annual sessions, making them a popular choice in many aesthetic clinics. Consulting with healthcare professionals is key to selecting the most suitable treatment approach for individual needs.